Pre-pubertal exposure with phthalates and bisphenol A and pubertal development. - Monika Kasper-Sonnenberg; Jürgen Wittsiepe; Katharina Wald; Holger M Koch; Michael Wilhelm (PLoS ONE, 2017)
Epidemiological studies indicate associations between childhood exposure with phthalates and bisphenol A (BPA) and the pubertal development. We examined associations between the pre-pubertal phthalate and BPA body burden and the longitudinally assessed sexual maturation of eight- to thirteen-year-old children.We started with eight- to ten-year-old children in the baseline study and quantified phthalate metabolites and BPA in 472 urine samples (250 boys; 222 girls; mean age: 8.8 years). Associations between the pubertal development, assessed in three annual follow-up studies by Puberty Development scale questionnaires (PD scales), and the chemical exposure from the baseline visit were longitudinally analyzed with generalized estimation equations.The number of children with both chemical measures and PD scores (calculated from the PD scales) was 408. In the third follow-up, 49% of the girls and 18% of the boys had reached mid-puberty. For girls, we observed a delayed pubertal development with the di-hexyl-ethyl phthalate (DEHP) metabolites (β: -0.16 to -0.23; p ≤ 0.05 or p ≤ 0.1), mono-n-butyl phthalate (β: -0.15; 95% CI: -0.31; 0.01), mono-benzyl phthalate (β: -0.11; 95% CI: -0,24; -0,01), and mono-ethyl phthalate (MEP) (β: -0.15; 95% CI: -0.28; -0.01). In addition, significant non-linear associations of the DEHP metabolites and BPA with the PD scores were found, when their quadratic effects were included in the GEE models. In boys, no consistent relationships between the PD scores and the chemicals were detected except of an accelerated development with the ∑DEHP metabolites (β: 0.16; 95% CI: -0.02; -0.34).We found indications that pre-pubertal exposures with phthalates and BPA were associated with pubertal timing in children, particularly in girls. For boys, associations were inconsistent, and not necessarily in line with the known anti-androgenicity of some phthalates during prenatal exposure.